Association of body fat percentage with kidney stone Disease: a cross-sectional and longitudinal study among bus drivers - Xujuan Zheng; Qianqian Chen; Yanxia Wu; Juan Xiong (BMC, 2023)
Abstract Background The association between body fat percentage (BFP) and kidney stone disease (KSD) among bus drivers has not been explored in the existing literature. Thus, this study was conducted to explore the influence of BFP on the risk of KSD as well as KSD development for bus drivers to fill the research gap. Methods A cross-sectional and longitudinal cohort study was designed. In total, 3433 bus drivers were included in the cross-sectional analyses, and 1864 bus drivers without KSD at baseline and with regular follow-up were included in the longitudinal cohort study. Results During a median follow-up of 2.9 years, KSD occurred in 15.0% of bus drivers. Multivariate logistic analysis found that each 5% higher BFP was not only significantly related with higher odds of KSD (odds ratio [OR] = 1.48), but also associated with higher odds of developing KSD (OR = 1.27). The risk of prevalent KSD in obesity group based on BFP was 2.47 times of the normal group; and the corresponding risk of developing KSD was 1.61 times. For obesity bus drives with age < 40, the corresponding risk increased to 4.54 times. Conclusion Bus drivers were reported to have a high prevalence of KSD as well as development of KSD. As a significant predictive factor for KSD, BFP can be used to monitor and prevent bus drivers from kidney stone formation. Bus drivers in obesity group based on BFP, especially with age < 40 years should become priority subjects for targeted prevention.